2022
DOI: 10.1097/md.0000000000029070
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of sleep disorders with long-term complications and health-related quality of life in people with well-controlled human immunodeficiency virus

Abstract: Although sleep disorders are common in patients with human immunodeficiency virus (HIV) infection, they have not been adequately evaluated under currently advanced treatments, mainly with integrase strand transfer inhibitors. However, the relationship of sleep disorders with long-term complications and quality of life (QOL) status in patients infected with HIV is still poorly understood. Such associations are important in the management of outpatients with HIV. Hence, this study aimed to evaluate these associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The prevalence of each syndrome was 15.6, 26.8, 12.1 and 18.1%, respectively. QOL was reported to be fair or poor in 57.7% patients, the median VACS Index score was 22 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and the median estimated risk of all-cause 5-year mortality according to the VACS Index was 7.8% (5.8-11.3). Differences by sex are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of each syndrome was 15.6, 26.8, 12.1 and 18.1%, respectively. QOL was reported to be fair or poor in 57.7% patients, the median VACS Index score was 22 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and the median estimated risk of all-cause 5-year mortality according to the VACS Index was 7.8% (5.8-11.3). Differences by sex are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among the four geriatric syndromes evaluated, the only one associated with higher risk of all-cause 5-year mortality was cognitive impairment (24 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs. 18 [17][18][19][20][21][22][23][24][25][26][27][28][29], P = 0.01).…”
Section: Effect Of Frailty Comorbidity and Geriatric Syndromes On Mor...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that concerns about appearance-related side effects underlay psychological distress, depression, and ART non-adherence among PLWH [ 47 , 48 ]. Sleep-related issues, such as insomnia or hypersomnia, usually associated with extreme fatigue, were also common among virologically suppressed PLWH or long-term ART [ 49 , 50 , 51 ]. HIV-related sleep disturbances have been linked to psychological disturbances and pain [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EMA study previously discussed also assessed mood and found that both subjective and objective sleep were associated with next-day depressive symptoms [30 && ]. Worse subjective sleep from PSQI questionnaires has also been associated with worse mental component scores of HRQoL in men in Japan (n ¼ 45 PWH) [32], more depressive symptoms in Ethiopia (n ¼ 399 PWH) [33], and more depressive and anxiety symptoms in women in the United States (n ¼ 1583 PWH) [34]. Another study in Nigeria (n ¼ 406 PWH) showed no association between PSQI scores and depressive symptoms, but showed an association between short sleep duration (a component of RU-SATED sleep health dimensions) and depressive symptoms [35].…”
Section: Depression and Anxietymentioning
confidence: 99%